Plasmodium falciparum variant erythrocyte surface antigens: a pilot study of antibody acquisition in recurrent natural infections - Schieck, Elise; Rippert, Anja (Malaria journal, 2017)
During intra-erythrocytic replication Plasmodium falciparum escapes the human host immune system by switching expression of variant surface antigens (VSA). Piecemeal acquisition of variant specific antibody responses to these antigens as a result of exposure to multiple re-infections has been proposed to play a role in acquisition of naturally acquired immunity.
Gesehen am 04.05.2018